Justification of production technology of chopped products using structured emulsions - Нечепуренко, Кристина Борисівна; Пивоваров, Павло Петрович (Technology audit and production reserves, 2013)
One of the most important problems of modern science is obtaining of materials with the specified mechanical properties and structure. The use of alginate emulsions with the residues of calcium is a promising raw material for the production of structured products. Under certain conditions, the use of AlgNa and slightly soluble salts CaSO4 in a new technology is expedient that will allow to control and manage the process of gelation in the technological flow of the manufacture of new products. The wide range of new technologies, including emulsification of various raw materials, namely polysaccharides, is used at this stage of development of food technology for the production of fundamentally new goods. The studied emulsifying ability of sodium alginate is reduced to the given dependence of the point of phase inversion on the concentration of sodium alginate and viscosity of the suspension. Generalization of analytical and experimental studies on justification of technological parameters of production of the thermo-stable structured emulsion allowed determining rational parameters of production of the latter in a part of prescription composition and modes of separate technological operations. As a result, we developed a principal technological scheme of production of minced meat products with the structured emulsion.